Logging damage and injured tree mortality in tropical forest management. (25th January 2019) - van der Werf, Edwin; Indrajaya, Yonky; Mohren, Frits; van Ierland, Ekko C.
Abstract: Using insights from the forest ecology literature, we analyze the effect of injured trees on stand composition and carbon stored in above‐ground biomass and the implications for forest management decisions. Results from a Faustmann model with data for a tropical forest on Kalimantan show that up to 50% of the basal area of the stand before harvest can consist of injured trees. Considering injured trees leads to an increase in the amount of carbon in above‐ground biomass of up to 165%. These effects are larger under reduced impact logging than under conventional logging. The effects on land expectation value and cutting cycle are relatively small. The results suggest that considering injured trees in models for tropical forest management is important for the correct assessment of the potential of financial programs to store carbon and conserve forest ecosystem services in managed tropical forests, such as reducing emissions from deforestation and forest degradation and payment for ecosystem services. Recommendations for Resource Managers Considering the role of injured trees is important for managing tropical forests These trees can cover up to 50% of basal area and contain more than 50% of the carbon stored in above‐ground biomass Reduced impact logging leads to a larger basal area of injured trees and more carbon stored in injured trees than conventional logging Injured trees play an important role when assessing the potential for carbon storage in the context of payment for forest ecosystem services.